Experimental Warming Reduces Survival, Cold Tolerance, and Gut Prokaryotic Diversity of the Eastern Subterranean Termite, Reticulitermes flavipes (Kollar) - Arango, Rachel A.; Schoville, Sean D.; Currie, Cameron R.; Carlos-Shanley, Camila (Frontiers in Microbiology, 2021)
Understanding the effects of environmental disturbances on insects is crucial in predicting the impact of climate change on their distribution, abundance, and ecology. As microbial symbionts are known to play an integral role in a diversity of functions within the insect host, research examining how organisms adapt to environmental fluctuations should include their associated microbiota. In this study, subterranean termites (Reticulitermes flavipes (Kollar)) were exposed to three different temperature treatments characterized as low (15 °C), medium (27 °C), and high (35 °C). Results suggested that pre-exposure to cold allowed termites to stay active longer in decreasing temperatures but caused termites to freeze at higher temperatures. High temperature exposure had the most deleterious effects on termites with a significant reduction in termite survival as well as reduced ability to withstand cold stress. The microbial community of high temperature exposed termites also showed a reduction in bacterial richness and decreased relative abundance of Spirochaetes, Elusimicrobia, and methanogenic Euryarchaeota. Our results indicate a potential link between gut bacterial symbionts and termite’s physiological response to environmental changes and highlight the need to consider microbial symbionts in studies relating to insect thermosensitivity.